Odpowiedzialność członka rady nadzorczej na podstawie art. 296 k.k. - Marcin Piotrowski (Studia i Materiały)
The present study is to analyze the constituent elements of art. 296 of the Criminal Code in the context of liability of the members of the supervisory board. For this purpose, the author attempts to synthetic approximation of the current achievements of the doctrine and jurisprudence, to define the mark, “dealing with financial affairs or business”. Analysis of the collected material reveals some discrepancies in the theory and practice. Finally, the author draws conclusions de lege ferenda aimed at developing a uniform interpretation of the concept of the mark “deals with financial affairs or business” including also supervision.